Morocco : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report ;, 2010)
Morocco's strong starting position, reflecting macroeconomic and structural reforms introduced over the last decade, has given the country greater room to maneuver in its policy response. The direct impact of the global crisis on Morocco has been limited, primarily affecting Morocco through real channels. Exports, tourism receipts, remittances, and foreign direct investment (FDI) have all declined primarily owing to the slowdown in Europe. In particular, Morocco has low public debt and low inflation, and the financial system is sound, with little exposure to international markets.